Fuzzy uncertainty analysis and reliability assessment of aeroelastic aircraft wings - Michael Friswell (The Aeronautical Journal, 2020)
In the present study, fuzzy uncertainty and reliability analysis of aeroelastic aircraft wings are investigated. The uncertain air speed and structural parameters are represented by fuzzy triangular membership functions. These uncertainties are propagated through the wing model using a fuzzy interval approach, and the uncertain flutter speed is obtained as a fuzzy variable. Further, the reliability of the wing flutter is based on the interference area in the pyramid shape defined by the fuzzy flutter speed and air speed. The ratio between the safe region volume and the total volume of the pyramid gives the reliability value. Two different examples are considered—a typical wing section, and a clean wing—and the results are given for various wind speed conditions. The results show that the approach considered is a low-cost but suitable method to estimate the reliability of the wing flutter speed in the presence of uncertainties.